The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2147/opth.s40454
|View full text |Cite
|
Sign up to set email alerts
|

Long-term bladeless LASIK outcomes with the FS200 Femtosecond and EX500 Excimer Laser workstation: the Refractive Suite

Abstract: Video abstract Video

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 22 publications
4
24
0
3
Order By: Relevance
“…Excimer laser systems have recently been developed with innovative features, such as high repetition rates (400 and 500 Hz) and customized ablation profiles 1,6,1114. These enhanced features have improved the effectiveness and safety of LASIK surgery, thus making treatment possible for a broad range of patients, including those with moderate-to-relatively high hyperopia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excimer laser systems have recently been developed with innovative features, such as high repetition rates (400 and 500 Hz) and customized ablation profiles 1,6,1114. These enhanced features have improved the effectiveness and safety of LASIK surgery, thus making treatment possible for a broad range of patients, including those with moderate-to-relatively high hyperopia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that higher repetition rates may provide better ablation quality vs slower systems 15. This improvement in ablation quality is thought to be due to a decrease in stromal dehydration, flap shrinkage, fixation fatigue, and sensitivity to eye movements 1,2,16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Они установили, что через 3 месяца острота зрения оказалась выше 1,0 в 94,7% случаев, оставаясь таковой в сроки до 12 месяцев [38]. Аналогичные данные были получены Han и соавт.…”
Section: исходы в раннем и отдаленном периодеunclassified
“…14,15 Reports from the past 15 years have shown continued improvement in safety and accuracy with the use of wavefront-guided and wavefront-optimized systems being used to treat myopic astigmatism as high as −10.00 to −12.00 D. These trials have reported up to 100% of eyes achieving refractions within 1 D of emmetropia. 1618 …”
Section: Lower-order Aberrationsmentioning
confidence: 99%